Musicalidade métrico tonal: condições primeiras para a comunicação verbal sobre a música - Moraes, Marcos Ribeiro de (2003)
Most of the premises on which tonal music elementary theory is based are rooted in a secular historical process which consists of a literal description of the visual signs of music notation. Such notation tends to make us believe that its constitutive features are there, virtually raised to the position of the musical sign, representing musical features and properties of its object the musical sounds. Thus, the two main attributes or parameters of sound represented in the notation, i.e., pitch and duration, are then accepted inside the group pitch, intensity, tone color and duration as parameters of music. Thus, elementary music theory tends to recognize in the liaison sound-notation, music semiosis itself, which we are inclined to complete with the locus of the interpretant, which is often filled in with verbal narratives. Yet visual signs are extra-musical, thus being, strictly speaking, external to the scope of the investigation on the semiotic functioning of music. Once left with sound alone, we can recognize its status, not as an object, but as a sign (representamen), which demands an object for itself, in other words, something this sound stands for. Along these lines, it is claimed in this study that that which are called notes in a melody are signs of an indexical kind, which stand for time vs. space loci. It is these loci which are the objects in music semiosis. As for pitch, the sounds would have the semiotic property of indicating/representing specific vertices of an spatiality which, homologically, can be represented by a heptagonal form whose sides are proportional to 2-2-1-2-2-2-1, that is, the Diatonic Form. As for rhythm, we shall claim that the instant of the coming-into-being of, i.e., the inchoative gesture that initiates a sound not the duration of the sound has the semiotic property of indicating/representing a point (a when , not a how much ), within a field of temporality inaugurated by a hierarchic set of pulsations. Given the appropriate conditions, that complex of pulsations could be understood as that which accounts for the fundamental syntax of tonal music.